1999
DOI: 10.1159/000024063
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Human IgG4 Antibody, BAB2, with Specificity for the Major Birch Pollen Allergen, Bet v 1 in Escherichia coli: Recombinant BAB2 Fabs Enhance the Allergic Reaction

Abstract: Background: Antigen recognition by antibodies of different isotypes can result in completely different effects as exemplified by Type I allergy. While the IgE–antibody–mediated release of biological mediators constitutes the immunopathological basis for the immediate symptoms observed in allergic patients, allergen–specific IgG antibodies are thought to have protective effects. Methods: Cell lines secreting five human monoclonal IgG antibodies (BAB1–BAB5) with specificity for the major birch pollen allergen Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Meanwhile, IgG is critical to the success of allergen-specific immunotherapy . IgG-binding epitopes can affect the binding of IgE to its antigenic epitope . Therefore, the binding of B-cell linear epitopes of LYS to IgG should be equally concerned about.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, IgG is critical to the success of allergen-specific immunotherapy . IgG-binding epitopes can affect the binding of IgE to its antigenic epitope . Therefore, the binding of B-cell linear epitopes of LYS to IgG should be equally concerned about.…”
Section: Discussionmentioning
confidence: 99%
“…41 IgG-binding epitopes can affect the binding of IgE to its antigenic epitope. 42 Therefore, the binding of B-cell linear epitopes of LYS to IgG should be equally concerned about. Among the seven IgE-binding linear epitopes mapped by the dot-blot assay, AA18−22, AA63−73, AA75−79, and AA115−117 were highly coincident with the predicted results.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a precedent in the case of the antibody BAB2 against a dominant birch pollen allergen, Bet v 1 58 . BAB2 and, notably, its Fab enhanced binding of Bet v 1 to IgE and caused immediate-type hypersensitivity reactions in human skin.…”
Section: Discussionmentioning
confidence: 99%
“…BAB2 and, notably, its Fab enhanced binding of Bet v 1 to IgE and caused immediate-type hypersensitivity reactions in human skin. The authors suggested that enhancing antibodies could account for the failure of specific allergen immunotherapy 58, 59, 60. Although enhancing antibodies are relatively rare, they might be important because their activity might “win” in competition with an excess of blocking antibodies.…”
Section: Discussionmentioning
confidence: 99%